Notification of Child Abuse by Proffessionals in the Community of Madrid: Percepción Vs. Realidad del uso de las Hojas de Notificación de Maltrato y Registro - Ruiz-Fincias, Mª Inmaculada; Grimaldo-Santamaría, Rolando-Oscar; Fuentes Essola, Julia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This research analyses the method of reporting suspected situations of child abuse, before the entry into force of the new law for the protection of children and adolescents modified the procedure. 138 professionals from the Community of Madrid, belonging to the professional fields mentioned in the law, participated in the study. They responded on their perception and effective use of the current notification forms. The results obtained indicate that no professional field habitually uses the common notification method mentioned in the law, despite the fact that most of them consider it to be useful, as well as the lack of a unified protocol.